Novel Cell Preservation Technique to Extend Bovine In Vitro White Blood Cell Viability. - Emilie L Laurin; Shawn L B McKenna; Javier Sanchez; Horacio Bach; Juan Carlos Rodriguez-Lecompte; Marcelo Chaffer; Greg P Keefe (PLoS ONE)
Although cell-mediated immunity based diagnostics can be integral assays for early detection of various diseases of dairy cows, processing of blood samples for these tests is time-sensitive, often within 24 hours of collection, to maintain white blood cell viability. Therefore, to improve utility and practicality of such assays, the objective of this study was to assess the use of a novel white blood cell preservation technology in whole bovine blood. Blood samples from ten healthy cows were each divided into an unpreserved control sample and a test sample preserved with commercially-available cell transport medium. Samples were maintained at room temperature and stimulated with the mitogens pokeweed and concanavalinA, as well as with interleukin-12 p40. Stimulation was completed on days 1, 5, and 8 post-sampling. Viability of white blood cells was assessed through interferon gamma production determined with a commercial enzyme linked immunosorbent assay. In addition, mononuclear cell viability was assessed with propidium iodide flow cytometry. Greater interferon gamma production was observed on days 5 and 8 post-collection in preserved samples, with both pokeweed and concanavalinA stimulating positive interferon gamma production on day 5 post-collection. A greater proportion of the amount of interferon gamma produced on day 1 continued to be produced on days 5 and 8 post-collection with concanavalinA stimulation (with or without interleukin 12) as compared to pokeweed stimulation. Additionally, viable mononuclear cells were still present at eight days post-collection, with a higher mean proportion detected at days 5 and 8 in all stimulated preserved samples. This practical and simple method to extend in vitro white blood cell viability could benefit the efficient utilization of cell-based blood tests in ruminants.